The Haptic Experience and its Impact on Purchase Decision in the Retail Context: A Comparative Study Between Augmented Reality and In-Store Haptic Experience - Al Maassarani, Mohamad (2024)
The study aims to examine and evaluate the haptic experience of augmented reality (AR) and in-store shopping and its influence on purchase decisions. The objectives are divided into defining haptic experience, to determine whether AR haptic experience delivers a better impact on purchase decisions in the retail sector and to determine whether in-store haptic experience delivers a better impact on purchase decisions in the retail sector. Furthermore, to find whether consumers behaviour after the Covid-19 pandemic have changed the preference of the purchase channel towards experience the haptic sensory. The study will follow the positivist research philosophy to collect primary data from retail consumers across the UK. This development paper aims to contribute towards the retailing customer experience literature and to the customer behaviour with respect to new innovative technologies.